(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The natural pre-requisites for the occurrence of floods and mudslides in the basin of the middle course of the Debed River, in the area from the mouth of the Dzoraget River to Ayrum, where on May 25–26, 2024, as a result of heavy precipitation (60% of the monthly norm), a severe flood occurred with significant destruction and even human casualties. These pre-requisites are the presence of exposed and steep slopes, a large number of ravines, easily eroded gravel-sandy loam and gravel-loamy soils, heavy rainfall, often accompanied by large hail. The greatest predisposition to the supply of water and solid components for the formation of floods and mudflows is characteristic of the left bank of the Debed River basin, especially the Lalvar, Yeritsvank and Kachachkut Rivers. The right bank is almost completely forested, here only Shnokh and Kistum Rivers has some corresponding potential due to the large number of ravines in their upper reaches. According to the method of V.P. Filosofov, the order of all rivers of the Debed River basin from the source of the Pambak River to the state border at Ayrum is determined. The fifth order has 15 rivers, the sixth order has 6 rivers (Lernajur, Tandzut, Alarex and Martz – on the right bank; Dzoraget and Chichkan – on the left bank), the seventh order is the Debed River (these orders correspond to a 1:25 000 scale map). To prevent the destruction of roads, it is proposed to strengthen the concave sections of the shore with capital concrete walls at the bends of the riverbed or by sketching large concrete blocks. At the same time, for less water intake in heavy rains from the slopes into the watercourses, it is necessary to cover the exposed slopes of the left bank.